Effect of Yoga on Lung Function Test - Vanita Sharma; Naresh Chander Sharma; Ritu Gupta; Megha Kapoor; Shazia Chowdhary (Dr. Annil Mahajan, 2022)
Background: Yoga is an ancient Indian system and largest surviving philosophical system in the world. It is a novel and emerging discipline in broad category of mind-body medicine. Yoga, a spiritual discipline, induces positive health and its effect on lung function test can be used clinically as a therapeutic intervention in lung diseases like asthma. Objective: The study was conducted to assess the effect of yoga on dynamic lung volumes. Results: The lung function tests were conducted on 50 healthy male and female controls not practicing yoga in the age group of 30-50 years and sex and age-matched 50 healthy subjects practicing yoga for 5 years. The lung volumes recorded on electronic Medspiror were forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), maximum voluntary ventilation (MVV), peak expiratory flow rate (PEFR), forced expiratory volume in 3 seconds (FEV3) respiratory rate (RR) and breath holding time (BHT). The study demonstrates increase in FVC, FEV1, MVV, PEFR, FEV3 and breath holding time and decrease of respiratory rate in yoga performers. Conclusion: Yoga has a therapeutic value and doctor with yogic attitude is likely to transmit to the patient a positive attitude and calm disposition to achieve better results in healing various diseases with less medication.